Multicomponent Polymeric Materials - Kim, Jin Kuk; Thomas, Sabu; Saha, Prosenjit (Springer Series in Materials Science,, 2016)
The book offers an in-depth review of the materials design and manufacturing processes employed in the development of multi-component or multiphase polymer material systems. This field has seen rapid growth in both academic and industrial research, as multiphase materials are increasingly replacing traditional single-component materials in commercial applications. Many obstacles can be overcome by processing and using multiphase materials in automobile, construction, aerospace, food processing, and other chemical industry applications. The comprehensive description of the processing, characterization, and application of multiphase materials presented in this book offers a world of new ideas and potential technological advantages for academics, researchers, students, and industrial manufacturers from diverse fields including rubber engineering, polymer chemistry, materials processing and chemical science. From the commercial point of view it will be of great value to those involved in processing, optimizing and manufacturing new materials for novel end-use applications. The book takes a detailed approach to the description of process parameters, process optimization, mold design, and other core manufacturing information. Details of injection, extrusion, and compression molding processes have been provided based on the most recent advances in the field. Over two comprehensive sections the book covers the entire field of multiphase polymer materials, from a detailed description of material design and processing to the cutting-edge applications of such multiphase materials. It provides both precise guidelines and general concepts for the present and future leaders in academic and industrial sectors.